Synthesis of Platinum Particles from H2PtCl6 with Hydrazine as Reducing Agent - Beyribey, Berceste; Corbacioglu, Burcu; Altin, Zehra (GAZI UNIV, 2009)
Platinum nanoparticles were obtained by chemical reduction of hexachloroplatinic acid (H2PtCl6) with hydrazine at various temperature and pH values. Reducing agent was chosen depending on the oxidation reactions and potential values of chemical materials used in the experiment. The aim of this study was to investigate the effects of temperature and pH on the structure of platinum particles. The morphology of platinum nanoparticles was investigated by JEOL, JSM-5410LX scanning electron microscope (SEM). Malvern Zetasizer 3000 HSA was used to determine size and zeta potential of platinum nanoparticles. The parameters that correspond to the production of minimum size platinum particles were obtained in addition the corresponding distribution of particle size were determined. These parameters were assumed to be the optimum conditions to obtain platinum nanoparticles from H2PtCl6 using hydrazine as reducing agent.
Keywords: Pt nanoparticle; H2PtCl6; Hydrazine; Chemical reduction; PT/C CATALYSTS; CARBON; NANOPARTICLES; ELECTRODEPOSITION; ELECTROCATALYSIS; (NH4)(2)PTCL6; REDUCTION; PALLADIUM; Science & Technology - Other Topics